2010
DOI: 10.1007/s00299-010-0903-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ascorbate peroxidase genes expressed in resistant and susceptible wheat lines infected by the cereal cyst nematode, Heterodera avenae

Abstract: Changes in ascorbate peroxidase (APX) enzyme activity in response to nematode (Heterodera avenae) attack were studied in roots of three hexaploid wheat lines carrying Cre2, Cre5, or Cre7 nematode resistance genes and the susceptible Triticum aestivum cv. Anza. A spectrophotometric analysis was carried out with root extracts of infected plants 4, 7, 11, and 14 days after nematode inoculation using uninfected plant as control. APX induction in infected resistant genotypes was similar and higher than in the susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 58 publications
(72 reference statements)
2
20
0
Order By: Relevance
“…They confirmed that SA inducible PR-1(P4) was a hallmark for the cultivar resistance conferred by Hero A against PCN and that nematode parasitism resulted in the inhibition of the SA signaling pathway in the susceptible cultivars. Similar effects were found in resistant line of hexaploid wheat carrying Cre2 gene, which showed upregulation of ascorbate peroxidase coding gene in response to cereal cyst nematode ( H. avenae ) when compared with the expression in the susceptible lines (Simonetti et al, 2010). …”
Section: Plant Natural Resistance Genessupporting
confidence: 65%
“…They confirmed that SA inducible PR-1(P4) was a hallmark for the cultivar resistance conferred by Hero A against PCN and that nematode parasitism resulted in the inhibition of the SA signaling pathway in the susceptible cultivars. Similar effects were found in resistant line of hexaploid wheat carrying Cre2 gene, which showed upregulation of ascorbate peroxidase coding gene in response to cereal cyst nematode ( H. avenae ) when compared with the expression in the susceptible lines (Simonetti et al, 2010). …”
Section: Plant Natural Resistance Genessupporting
confidence: 65%
“…Cereal cyst nematode (CCN), Heterodera avenae, is one of the most important cereal pathogens worldwide, causing yield losses and decreased grain quality (Long et al, 2013;Kumar et al, 2014). A better understanding of the mechanisms underlying the interactions between CCN and its hosts is important for the development of new control strategies against this pathogen (Simonetti et al, 2010). However, studying the complex molecular interactions between CCN and its host is challenging due to the lack of a suitable model pathosystem.…”
Section: Introductionmentioning
confidence: 99%
“…Montes et al [13] analyzed the activities of peroxidase and superoxide dismutase in the roots of resistant and susceptible cultivars of wheat with respect to infestation by the nematode, Heterodera avenae and found that the resistant variety exhibited enhanced activities in comparison to the susceptible ones. Similarly, Simonetti et al [14,15] also showed that ascorbate peroxidase and apoplastic peroxidase genes are upregulated in wheat lines resistant to Heterodera avenae compared to susceptible cultivars. Uehara et al [16] made a comparative microarray analysis of the compatible and incompatible interaction in tomato cultivars with respect to the interaction with the potato cyst nematode (PCN; Globodera rostochiensis ) at early stages.…”
Section: Discussionmentioning
confidence: 91%